2018
DOI: 10.1186/s13104-018-3142-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of hematological reference intervals for healthy adults in Asmara

Abstract: ObjectivesClinical laboratory reference intervals used in a specific area should be derived from the local population as they are influenced by many factors. The purpose of this quantitative cross sectional study was to establish hematological reference intervals for healthy adults in Asmara and to determine whether the currently used reference interval do represent the adult population in the city. In addition, the established reference intervals were compared to findings from similar studies conducted in sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
3
11
5
Order By: Relevance
“…In addition to that, menstrual period may lead down women RBC count. Our findings comply with several studies [10,12,[20][21][22][23][24]. Conversely, females had higher levels of MCV and MCH and involved those of 6-15 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to that, menstrual period may lead down women RBC count. Our findings comply with several studies [10,12,[20][21][22][23][24]. Conversely, females had higher levels of MCV and MCH and involved those of 6-15 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…whereas the females scored a mean of 32.4g/dL RBCs [9]. One can notice that apart from the MCHC, all the current results are lower than the population-based study.…”
Section: Discussioncontrasting
confidence: 82%
“…This study found the RIs for RBC, Hb, HCT, MCV and MCH to be higher in males compared to females whereas WBC and platelet counts were higher in females compared to males as consistent with previous reports in other African countries [ 8 , 18 22 ]. The differences in RIs based on sex may be linked to the effect of menstruation and its associated increased demand for iron, differences in androgen hormones (testosterone and oestrogen) and the extent to which erythropoiesis and megakaryopoiesis are regulated in males and females [ 21 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%